Selective Kirchner medium in the culture of specimens other than sputum for mycobacteria. - Mitchison, D A (1983)
Over a two-year period, 2949 non-sputum specimens were cultured on two slopes of Löwenstein-Jensen (LJ) medium, two bottles of Kirchner liquid medium, made selective by adding polymyxin B, carbenicillin, trimethoprim and amphotericin B, and a selective 7H11 agar slope. Pus and CSF were inoculated into this set without prior treatment, but other specimens were decontaminated with sulphuric acid. Tissues and fluids were also inoculated without decontamination into additional selective media. The use of the selective media as well as the LJ slopes increased the yield of specimens with cultures of tubercle bacilli from 34 to 53 and decreased specimens with all media contaminated from 34 to 2. Results almost as good, 52 positive specimens and five totally contaminated, would have been obtained by the addition of a single selective Kirchner bottle to the two LJ slopes, and this is recommended for routine use.